Structure and Strength of Dispersion-Hardened Composite Foils (Films) Based on Iron and Nickel - Il'insky, A. I.; Barmin, A. E.; Lyabuk, S. I. (Institute for Single Crystals, 2013)
Size effects, thermal stability, and relaxation resistibility of Fe and Ni nano-composite dispersion-hardened foils (films) were studied based on the correlation between structure and physical-mechanical properties. The strengthening phase (tungsten, oxides) content was about 1vol.%. Non-monotonic character of grain size influence on physical-mechanical properties and inhomogeneous distribution of strengthening phase within a grain were analyzed. The reasons of nano-composite high thermal stability were considered. The factors determining the nano-composite relaxation resistibility and resources for its increasing were revealed.

На основі кореляції структури і фізико-механічних властивостей розглянуті результати вивчення розмірних ефектів, термічної стабільності та релаксаційної стійкості дисперснозміцнених фольг (плівок) нанокомпозитів Fe і Ni. Зміст зміцнюючих фаз (вольфрам, оксиди) становило близько 1 об. %. Проаналізовано немонотонний характер впливу розміру зерна на фізико-механічні властивості, а також неоднорідний розподіл зміцнюючої фази в межах зерна. Розглянуто причини високої термічної стабільності нанокомпозитів. Виявлено фактори, що визначають релаксаційну стійкість нанокомпозитів та шляхи її підвищення.
Структура і міцневі характеристики фольг (плівок) дисперсно-зміцнених нанокомпозитів на основі заліза і нікелю
Keywords: nanocrystalline materials; vacuum condensates; segregation; thermal stability; нанокристалічні матеріали; сегрегація; вакуумні конденсати; термічна стабільність